Managing family conflict and resilience. Results of a universal socio-educative family drugs prevention program developed in school settings - Victoria Quesada-Serra; Maria-Antònia Gomila-Grau; Carmen Orte (Estudios sobre Educación, 2022)
This paper assesses changes in family conflict and resilience among families participating in a socio-educative short universal drug prevention program (PCF-U 11-14). A pre-post test quasi experimental design with control and experimental groups was implemented with 275 families. The work addresses the convenience of family training in social and parenting skills to strengthen families’ capacity to cope with difficulties and boosting family cohesion, but it also highlights the need to research deeper into the factors that affect parent and adolescent conflict to create new training strategies for families.